Ecologies of hope: transgressions and (trans)formations in/for Brazilian education - Aguiar, André Effgen; Oliveira, Grassinete C. de Albuquerque; Queiroz, Amilton José Freire de; Righi, Fernanda; Lomeli, Jafte Dilean Robles (The ESPecialist, 2024)
The thematic Dossiers from the 1st ELLAE International Congress - Transgressive teachings, solidary learning - for an ecology of languages-literatures-languages seek ecologies as practices and horizons of life, freedom, transformation as concepts that move the teaching-student process .